Preferred product characteristics for therapeutic vaccines to improve tuberculosis treatment outcomes: Key considerations from World Health Organization consultations. Issue 2 (10th January 2020) - Vekemans, Johan; Brennan, Michael James; Hatherill, Mark; Schrager, Lewis; Fritzell, Bernard; Rutkowski, Kathryn; De Vos, Beatrice; Zignol, Matteo; Thiry, Georges; Ginsberg, Ann M.; Walker, Barry
Abstract: Treating tuberculosis (TB) requires a multidrug course of treatment lasting 6 months, or longer for drug-resistant TB, which is difficult to complete and often not well tolerated. Treatment failure and recurrence after end-of-treatment can have devastating consequences, including progressive debilitation, death, the transmission of Mycobacterium tuberculosis – the infectious agent responsible for causing TB – to others, and may be associated with the development of drug-resistant TB. The burden on health systems is important, with severe economic consequences. Vaccines have the potential to serve as immunotherapeutic adjuncts to antibiotic treatment regimens for TB. A therapeutic vaccine for TB patients, administered towards completion of a prescribed course of drug therapy or at certain time(s) during treatment, could improve outcomes through immune-mediated control and even clearance of bacteria, potentially prevent re-infection, and provide an opportunity to shorten and simplify drug treatment regimens. The preferred product characteristics (PPC) for therapeutic TB vaccines described in this document are intended to provide guidance to scientists, funding agencies, public and private sector organizations developing such vaccine candidates. This document presents potential clinical end-points for evidence generation and discusses key considerations about potential clinical development strategies.